Effects of subchronic exposure to atrazine on zebrafish (Danio rerio) - Plhalova, L; Blahova, J; Mikulikova, I; Stepanova, S; Dolezelova, P; Praskoval, E; Marsalek, P; Skoric, M; Pistekova, V; Bedanova, I; Svobodova, Z (Polish journal of veterinary sciences, 2012)
The aim of this study was to investigate the effects of subchronic exposure to atrazine on fish growth and the development of histopathological changes in selected organs (gill, kidney, liver) in Danio rerio. Juvenile growth tests were performed on D. rerio according to OECD method No. 215. For 28 days, fish at an initial age of 30 days were exposed to the environmental atrazine concentration commonly detected in Czech rivers (0.3 microg/L) and a range of sublethal concentrations of atrazine (3.0, 30.0 and 90.0 microg/L). The results showed decreasing growth rates and morphological changes in the liver (dystrophic lesions of hepatocytes) at 90.0 microg/L of atrazine. The environmental concentration of atrazine in Czech rivers did not have any effect on fish growth and development of histopathological changes in D. rerio. The value of NOEC was 30.0 microg/L and the value of LOEC was 90.0 microg/L.
Keywords: herbicidy; dánio pruhované; Gills; atrazin; chování zvířat; Water Pollutants, Chemical; ledviny; Atrazine; játra; Animals; Dose-Response Relationship, Drug; Liver; Czech Republic; Drug Administration Schedule; žábry; zvířata; rozvrh dávkování léků; Rivers; Zebrafish; Behavior, Animal; Česká republika; vztah mezi dávkou a účinkem léčiva; chemické látky znečišťující vodu; Kidney; Herbicides; řeky